Medical Undergraduates’ Ability to Answer Problem-based Objective Questions Compared to Traditional Clinical Ones in Regional Anatomy - Yasmin, Farhana; Amin, Nahid Farhana (Mediscope, 2023)
Background: Anatomy is the most fundamental subject in undergraduate medical education and the curriculum is changing progressively for better outcomes for undergraduates. Clinical integration in learning Anatomy has been highlighted in the current curriculum. Therefore, analysis of the performance of the medical undergraduates on problem-based questions and traditional clinical objective questions on Regional Anatomy may provide an understanding of the recent teaching-learning-assessment trends in this subject and this type of research would help the teachers and curriculum planners to improve the teaching-learning-assessment pattern of Anatomy. Objective: To assess the ability of the medical undergraduates of Bangladesh to answer problem-based objective questions compared to traditional clinical objective written questions in Regional Anatomy. Methods: A total of 166 new third-year medical undergraduates participated in this research. Among them, eighty-three undergraduates participated to answer one hundred problem-based objective written questions and another eighty-three undergraduates participated to answer one hundred traditional clinical objective written questions in Regional Anatomy. The performance of the undergraduates was compared by the Mann-Whitney U test. Results: The performances of the medical undergraduates answering problem-based objective written questions were significantly poorer than those answering traditional clinical objective written questions. Conclusion: The result has shown that the performances of the medical undergraduates regarding problem-based objective questions are poorer than traditional clinical ones, most likely because they are not accustomed to the problem-based question, though it is the guideline of the curriculum. For better learning and assessment methods, the integration of problem-based questions is highly recommended in Regional Anatomy. Mediscope 2023;10(2): 78-88